Analysis of Motivation and Work Discipline in Implementation of the Duties of Army Soldiers in the Unit Yonif 623/Bwu in South Kalimantan - Priya Firmansyah; Veronika Santi Paramita (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
The objective of this research is to assess the level of motivation and work discipline among TNI AD troops in the Yonif 623 / BWU unit in South Kalimantan. The issue addressed in this study pertains to the suboptimal levels of motivation and work discipline, which can be attributed to several inhibitory influences. The objective of this research is to conduct a comprehensive examination and analysis of the impact of motivation and work discipline on the performance of TNI AD troops in the Yonif 623 / BWU unit. Furthermore, the study aims to identify the challenges encountered and evaluate the strategies employed to overcome these challenges. This study employs a descriptive analytical method with a qualitative approach. The data collection approaches employed include observations, interviews, and the examination of relevant documents. The informants are the Commander and a purposively selected group of soldiers. The findings indicated that the insufficient motivation and lack of work discipline among TNI AD soldiers in the Yonif 623 / BWU unit were attributed to multiple reasons, including the following: (1) The factors that influence job satisfaction can be categorized into four main areas: (1) Ability and HR, (2) Support received in terms of income, (3) Existence of work and workplace, and (4) Relationship with the organization.